Review of the genus Villa Lioy (Bombyliidae, Diptera) from Egypt, with descriptions of two new species - El-Hawagry, Magdi S.; Greathead, David J. (Zootaxa, 2006)
A review of the genus Villa Lioy in Egypt was carried out. Seven species were found, two of them are described as new, namely: V. efflatouni sp. nov. and V. stenozoides sp. nov.; V. aegyptiaca Engel is raised to species level (stat. nov.) and a lectotype designated; and V. bivirgata Austen and V. paniscoides Bezzi are recorded for the first time from Egypt. Another two species, V. cana (Meigen) and V. micrargyra (Walker) were previously recorded in Egypt. The study of type specimens showed that V. senecio (Loew), wrongly recorded from Egypt, is a synonym of V. ixion (Fabricius) syn. nov. A key, diagnoses, and illustrations of genitalia and wings of some species are provided.